2006
DOI: 10.1160/th05-06-0446
|View full text |Cite
|
Sign up to set email alerts
|

Combined genetic profiles of components and regulators of the vitamin K-dependent γ-carboxylation system affect individual sensitivity to warfarin

Abstract: We examined the influence of combined genotypes on interindividual variability in warfarin dose-response. In 100 anticoagulated patients we quantified the effects of polymorphisms in: CYP2C9, VKORC1, calumenin (CALU), gamma-glutamyl carboxylase (GGCX) and microsomal epoxide hydrolase (EPHX1) on warfarin dose requirements. The G(1542)C VKORC1 polymorphism was associated with decreased warfarin doses in the hetero- and homozygous mutant patients (21% and 50% lower, respectively; p < 0.0001). Warfarin daily dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
122
4
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 41 publications
9
122
4
2
Order By: Relevance
“…Although most of the variability observed in patients' response to warfarin may be attributed to genetic varations in VKORC1 (Mushiroda et al 2006;Schwartz and Stein 2006) that functions to regenerate reduced vitamin K (Rost et al 2004;Li et al 2004), polymorphisms in GGCX have also been indicated to have some association with inter-individual variation in warfarin maintenance-dose requirement (Shikata et al 2004;Chen et al 2005;Loebstein et al 2005;Wadelius et al 2005;Herman et al 2006;Kimura et al 2007;Vecsler et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the variability observed in patients' response to warfarin may be attributed to genetic varations in VKORC1 (Mushiroda et al 2006;Schwartz and Stein 2006) that functions to regenerate reduced vitamin K (Rost et al 2004;Li et al 2004), polymorphisms in GGCX have also been indicated to have some association with inter-individual variation in warfarin maintenance-dose requirement (Shikata et al 2004;Chen et al 2005;Loebstein et al 2005;Wadelius et al 2005;Herman et al 2006;Kimura et al 2007;Vecsler et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A single common VKORC1 SNP Ϫ1639/3673 AϾG defines VKORC1 haplotypes with increased sensitivity to warfarin (group A haplotypes, H1 and H2). [1][2][3][4][5][6][7][8][9] CYP2C9 is responsible for metabolism of Ͼ90% of S-warfarin, the more active enantiomer of warfarin. Two common allelic variants of CYP2C9 with reduced enzymatic activity (CYP2C9*2 and CYP2C9*3) have been associated with reduced metabolism of warfarin, lower required doses of warfarin to achieve adequate anticoagulation, and increased risk of adverse events when beginning warfarin therapy.…”
mentioning
confidence: 99%
“…However, following application of the Bonferroni M eff method to determine the significance cut point, and assuming independent contribution of each gene, only VKORC1 and the CYP SNPs remained significantly associated. G 11 A (R4Q) (rs2290228) in the CALU gene, that was associated with higher warfarin dose requirements in the study by Vecsler et al, 7 showed no association in the largely Swedish Wadelius 21 cohort; whereas 3' untranslated region (UTR) SNP (rs11653), a nonsynonymous SNP (rs2307040), and two intronic SNPs, rs339054 and rs1006023, showed marginal statistical significance. However, when all nominally associated genes were modeled and adjusted for variables with individual P values above 0.2 and low r 2 values, CALU was not found to be a significant contributor.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the association seen with rs2290228 in the Vecsler study, 7 we chose to examine a different allelic variant, A29809G (rs1043550), occurring in the 3'UTR region, based on the following rationale: (1) the ethnicity of Vecsler 7 study cohort that exhibited an increase in warfarin dose requirement as a factor of the rs2290228 allele did not align with that of the Northern European, Marshfield cohort whose heritage is predominantly German; (2) the minor allele frequency for rs1043550 is well represented in a Caucasian population; and (3) the study by Gonzalez-Conejero et al 8 observed that CALU A29809G (rs1043550) enhanced the effect of VKORC1 1173C>T on acenocoumarol dose in a statistically significant manner (P = 0.001) in a Spanish Caucasian population. Therefore, it was of interest to see if this allele would impact warfarin dose in our Caucasian, northern European cohort, especially among patients requiring higher warfarin dosing.…”
mentioning
confidence: 76%
See 1 more Smart Citation